Faktor Risiko Pekerjaan untuk Carpal Tunnel Syndrome pada Pekerja Kantoran - Christy E. I. Berhimpon; Andriessanto C. Lengkong; Eko Prasetyo (Medical Scope Journal, 2023)
Abstract: Carpal tunnel syndrome (CTS) is often reported as an occupational disease and a common problem among workers who often use their hands. The causes of CTS are considered multifactorial, involving both individual and occupational factors. Computer use is thought to be a risk factor for CTS. Using a computer keyboard is associated with wrist or hand pain, which is related with repetitive hand movements. However, the available evidence regarding the relationship between computer use or occupational risk factors and CTS is still controversial. This study aimed to determine the occupational risk factors for CTS in office workers. This was a literature review study. Data were searched from databases of Crossref and Google Scholar. The keywords were carpal tunnel syndrome, risk factor, ergonomic, occupation, computer office, workers The results obtained 10 articles reviewed according to predetermined inclusion and exclusion criteria. Work duration and work periods were referred to occupational risk factors for CTS. Awkward wrist/hand postures especially without mousepad supporting the hand or wrist, and repetitive movement were direct risk factors for CTS. In conclusion, risk factors for CTS among office workers are duration and period of working, awkward wrist/hand posture, and repetitive movement. Keywords: occupational risk factors; carpal tunnel syndrome; office workers.   Abstrak: Carpal tunnel syndrome (CTS) merupakan penyakit akibat kerja dan menjadi masalah umum di antara para pekerja yang sering menggunakan tangan. Penyebab CTS dianggap multifaktorial, yang melibatkan faktor individu dan pekerjaan. Penggunaan komputer diduga menjadi faktor risiko CTS. Penggunaan keyboard komputer dihubungkan dengan nyeri pergelangan tangan atau tangan, yang berkaitan dengan gerakan tangan berulang. Walaupun demikian, bukti yang tersedia perihal keterkaitan antara penggunaan komputer atau faktor risiko pekerjaan dan CTS masih kontroversial. Penelitian ini bertujuan untuk mengetahui faktor risiko pekerjaan terjadinya CTS pada pekerja kantoran. Jenis penelitian ini ialah suatu literature review menggunakan data- base Crossref dan Google Scholar dengan kata kunci carpal tunnel syndrome, risk factor, ergonomic, occupation, computer office, workers. Hasil penelitian mendapatkan 10 artikel yang ditelaah sesuai dengan kriteria inklusi dan eksklusi yang telah ditentukan. Durasi kerja dan periode kerja disebut sebagai faktor risiko pekerjaan untuk terjadinya CTS. Postur yang janggal, khususnya dikarenakan tanpa penggunaan mousepad penyangga tangan atau pergelangan tangan serta gerakan berulang saat menggunakan mouse dan mengetik menggunakan keyboard secara langsung menjadi faktor risiko terjadinya CTS. Simpulan penelitian ini ialah durasi dan periode kerja, postur tangan/pergelangan yang janggal, dan gerakan berulang merupakan faktor risiko pekerjaan untuk terjadinya CTS. Kata kunci: faktor risiko pekerjaan; carpal tunnel syndrome; pekerja kantoran